Peranan Polres Deli Serdang Dalam Pelaksanaan Diversi Untuk Anak Pelaku Tindak Pidana : Studi Keputusan Bupati Deli Serdang No. 2283 Tahun 2016 Tentang Tim Pelaksana Forum Diversi Dan Keadilan Restoratif Dalam Penanganan Anak Yang Berkonflik Dengan Hukum - Randy Anugrah Putranto; Madiasa Ablisar; Marlina Marlina; Edy Ikhsan (Universitas Sumatera Utara, 2019)
Abstract. The implementation of diversion in Deli Serdang Regency based on Law No. 11 of 2012 concerning the Child Criminal Justice System and Deli Serdang District Decree No. 2283 of 2016 concerning the Implementation Team of the Diversity and Restorative Justice Forum in Handling Children in Conflict with the Law in Deli Serdang Regency is an effort made to achieve the diversion goal optimally in the form of avoiding detention, avoiding labeling as a criminal, proposing interventions needed by victims or the perpetrators without going through a formal process and avoiding children from following the criminal justice process in order to avoid the negative influence and implications of the process. Keywords: children, criminal acts and diversity